Laulības šķiršanas īpatnības Latvijas teritorijā XIX-XX gs. - Straupeniece, Ilze (Latvijas Universitāte, 2007)
Diplomdarbā „Laulības šķiršanas īpatnības Latvijas teritorijā 19.-20. gadsimtā” ir pētīta un analizēta laulības šķiršanas institūta attīstība Latvijas teritorijā. Liela uzmanība tiek pievērsta laulības šķiršanas tiesiskajiem pamatiem, kā arī procesuālajai kārtībai laulības šķiršanas lietās un to īpatnībām pētāmajā laika periodā, tās pamatojot un saistot ar konkrēto vēsturisko un politisko situāciju Latvijas teritorijā. Pētījuma rezultātā tiek secināts, ka laulības šķiršanu reglamentējošās normas attīstoties un mainoties politiskajiem procesiem, kā arī izmaiņām sabiedrības domāšanā, tiek grozītas un pilnveidotas atbilstoši šīm izmaiņām sabiedrībā.

The development of institution of marriage dissolution within the territory of Latvia has been explored and analysed in this Diploma paper titled “The peculiarities of marriage dissolution within the territory of Latvia in 19 – 20 centuries”. In this Diploma paper a close attention has been directed to the legal grounds of marriage dissolution, rules of procedure on marriage dissolution cases and the peculiarities thereof within the time period explored, reasoning and regarding them to concrete historical and political situation, being there in the territory of Latvia within said time period. As a result of analysis, the conclusion has been made that the legal rules, regulating marriage dissolution, were being modified and improved in accordance with political evolution and changes in the mode of thinking of the society.
The peculiarities of marriage dissolution within the territory of Latvia in XIX-XX century
Keywords: Tiesības